ENT 530 Social Media Portfolio: Kasha Scarf / Siti Zulaikha Azhar - Azhar, Siti Zulaikha (2021)
Kasha Scarf is a sole proprietorship located at Parit 3 Sungai Haji Dorani 45300 Sungai Besar, Selangor. This business is run in owner’s house because it is only a small business. However, I, Siti Zulaikha binti Azhar as the owner of this business must want this business to continue to grow and produce more products of its own. Currently, Kasha Scarf only produces three products, namely Chiffon Eyelash Shawl, Bawal Cotton B45 and Bawal Cotton B50. This business is very concerned about the quality of their products and trying to grow this business and this subject opened my eyes to sell on social media in the right way. This business was developed in February 2020 but just sell in offline ways. The target of this business is university students because the prices set are suitable for university and college students as well. I hope this business can grow and help more people.